Tinjauan Strategi Wacana Kuasa Pemerintah dalam Tafsir Al-Qur’an Tematik Kementerian Agama RI (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2019)
The Thematic Al-Qur'an Interpretation of the Ministry of Religion (TQTKA) is a collective work or ijtiha> d Jama> ’i> the Indonesian Ministry of Religion team. The theme presented in TQTKA is in accordance with the anxiety of the people in this contemporary era, so that it is expected to provide answers to the problems of the people. In epistemology, TQTKA essentially departs from the functional paradigm, then interpretation is the science used to explain meaning, explore the law, and wisdom that is in the Koran. The orientation used by the government is prospective orientation, therefore the government always pays attention to social-social problems that exist in Indonesia. Judging from the method used in TQTKA is the interpretation of maudu> 'i> or thematic and patterned adabi ijtima’i>. Then the validity of TQTKA is seen from 3 theories; coherence theory, correspondence theory, and pragmatism theory.The strategy used by the government is to position TQTKA as a product of knowledge, while the interpretation team is an extension of the ruling government. Of course this relationship between power and knowledge necessitates the influence of even intervention. As the power relation defined by Michel Foucault that power relations as something that makes people obedient. Power relations is the concept of power relations, where the practices of power come from subjects on objects through various media. The strategy is conveyed through religious, state, culture, gender media, the fourth of which is packaged in the Qur'anic interpretation of TQTKA.